Beauty imagined a history of the global beauty industry - Jones, Geoffrey 1952- (Oxford University Press, 2015)
The global beauty business permeates our lives, influencing how we perceive ourselves and what it is to be beautiful. The brands and firms which have shaped this industry, such as Avon, Coty, Estee Lauder, L'Oreal, and Shiseido, have imagined beauty for us. This book provides an authoritative history of the global beauty industry from its emergence in the nineteenth century to the present day, exploring how today's global giants grew
Includes bibliographical references and index
Originally published in print: 2010
Keywords: Cosmetics industry / History